MODEL SOUVENIR SEBAGAI PENINGKATAN KUALITAS ESTETIS DAN VARIAN PRODUK PADA SENTRA KERAJINAN GEMBRENG PASAR KABANGAN LAWEYAN SURAKARTA - Cholis, Henri; Isnanta, Satriana Didik (Acintya, 2018)
This research entitled â€œSouvenir Models as an Improvement of Aesthetic Quality and Product Variety in Gembreng Crafts Center, PasarKabanganLaweyan Surakartaâ€ in general aimed to improve the quality and product variants in Gembreng Crafts Center, PasarKabanganLaweyan Surakarta, followed by aesthetic product variants that are able to represent the city of Surakarta as an increasing competitiveness in the global market. Â The specific purpose of this research is to develop the competitiveness of gembreng handicraft products with other souvenirs such as batik, wood or metal so as to attract the attention and interest of domestic and foreign tourists and indirectly also increase the income of the craftsmen.This research applied explorative exploratory research method. Therefore, it tends to be experimental; looking for novelty possibilities in the techniques and design of souvenir aesthetic products.Â  Data collection techniques undertaken by researchers were observations and in-depth interviews at the gembreng industry center in Pasar Kabangan Laweyan, Surakarta. The subject of this research was the gembreng craftsmen, with the aim of knowing the techniques they use and the techniques that can be explored for new products planned.Â  In addition, this study also interviewed some artists and culture bearers in Surakarta to find a visual image that can represent the city of Surakarta as a cultural city. Objects observed in this study were the results of the products that have been produced and the manufacturing techniques of handicraft products.Â  It is important to look for various possibilities for the development of the planned product designs. The existing data were validated by data reduction techniques and then they were analyzed. The results of this analysis were the basis for the development of souvenir product designs in the gembreng crafts center, Pasar Laweyan, Surakarta.The results of this development research were in the form of prototype gembreng-based souvenir products with a variety of possible variants, both the form and creativity. It is expected that the visual image of this product can represent the city of Surakarta as a cultural city.Â Keywords: souvenir, gembreng crafts,,SurakartaÂ